The Role of Analyze-Identify-Connect in Enhancing Students’ Conceptual Understanding in Mathematics: A Quasi-Experimental Approach - Ezekiel O Pelayo (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: The study aimed to compare the effects of AIC learning model and conventional method of teaching on students’ conceptual understanding in mathematics. Methodology: The study utilized a quasi-experimental design, with data on students’ conceptual understanding collected by a researcher-developed test aligned to NCTM standards. Data analysis was conducted using SPSS with ethical review and informed consent procedures in place. Main Findings: The findings demonstrate that the AIC learning model significantly enhances students' conceptual understanding in geometry, as evidenced by higher N-gain scores and a substantial effect size of 0.83 in the medium range. The experimental group outperformed the control group, shifting learning outcomes into a more effective range for conceptual development. This structured approach facilitates meaningful cognitive restructuring, marking a notable scientific contribution to mathematics education research. Novelty/Originality of this study: This study introduces the AIC learning model as a pedagogical framework that systematically promotes conceptual understanding and student engagement in mathematics classrooms. Theoretically, it advances instructional design by demonstrating how structured, interactive methods can facilitate cognitive restructuring and deeper learning processes. These contributions provide a foundation for further research on the sustained effect of such approaches and offer actionable guidance for educators seeking to enhance mathematics teaching.